Aplicativo móvil y la mejora en la visualización de catálogos de especies de flora y fauna, IIAP, Iquitos–2024 - Cabrera Rengifo, Anthony Leonardo (2025)
In developing this thesis, a mobile application was developed using the agile Scrum methodology, planning the product to improve the viewing and querying of the flora and fauna species catalogs managed by the Peruvian Amazon Research Institute (IIAP), located in Iquitos. The initiative primarily sought to optimize the user experience, streamline search times, and facilitate access to relevant information on Amazonian species. To this end, a system was designed to centralize information that was previously scattered across multiple folders hosted on IIAP servers, thus achieving a more organized, efficient, and accessible platform. The project focused on addressing three specific needs: improving user satisfaction when viewing species, reducing the time required to find information within the catalogs, and simplifying access to available data. Furthermore, this mobile application contributes to the conservation and protection efforts of Amazonian biodiversity, while promoting environmental education and raising public awareness. To measure the impact of this technological tool, a quantitative approach was used to assess changes in the user experience compared to the previous system. The research was considered applied, as a specific solution to an identified problem was proposed and implemented. Despite some limitations, the project proved feasible in terms of both time and financial resources.